STUDY OF HE SCIENTIFIC HERITAGE OF THE SCIENTIST-HISTORIAN M.KOZYBAEV: STUDY OF HE SCIENTIFIC HERITAGE OF THE SCIENTIST-HISTORIAN M.KOZYBAEV - Акерке, Кушкинбаева (Вестник ЗКУ, 2024)
The article analyzes the life path and research works on the scientific and pedagogical activities of the scientist academician Manash Kabashuly Kozybaev.  At the same time, the article examines the opinions and memories of the scientist’s contemporaries, friends, colleagues and government officials.